2001
DOI: 10.1007/s003300000736
|View full text |Cite
|
Sign up to set email alerts
|

En bloc excision of nonpalpable breast lesions using the advanced breast biopsy instrumentation system: an alternative to needle guided surgery?

Abstract: This study was prospectively conducted to evaluate the clinical potential of the advanced breast biopsy instrumentation (ABBI) system as an alternative to needle localization and open surgery in the management of nonpalpable breast lesions (NPBL). One hundred and eighty-six consecutive patients were referred for management of NPBL. Thirty-six underwent an ABBI procedure, offered as a first step before possible surgery for lesions which would in any case have required complete excision. The 18 patients with a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
4

Year Published

2002
2002
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 14 publications
0
8
0
4
Order By: Relevance
“…The literature reviewed shows the current status of controversy: except for Damascelli et al [16], the remainder of the radiologists are sceptical or clearly adverse to the procedure [2,3,4,5,6]. Surgeons are divided: some of them are enthusiastic about the procedure [17,18,19,20,21,22,23,24,25,26,27,28,29], but others not [7,8,9]. The reasons argued against the ABBI are multiple.…”
Section: Discussionmentioning
confidence: 92%
“…The literature reviewed shows the current status of controversy: except for Damascelli et al [16], the remainder of the radiologists are sceptical or clearly adverse to the procedure [2,3,4,5,6]. Surgeons are divided: some of them are enthusiastic about the procedure [17,18,19,20,21,22,23,24,25,26,27,28,29], but others not [7,8,9]. The reasons argued against the ABBI are multiple.…”
Section: Discussionmentioning
confidence: 92%
“…In an earlier study we confirmed that the ABBI method was a safe and accurate biopsy procedure. 20 We established that an ABBI excision was feasible and adequate for less than 40% (17/43) of the benign lesions that would otherwise have been surgically excised in our department, and for only 21% (11/53) of the nonpalpable mammograhically detected carcinomas. Many (62%) of the excised NPBL in that study were not amenable to an ABBI procedure, primarily due to technical limitations.…”
Section: Discussionmentioning
confidence: 90%
“…20 However, for invasive lesions we need to develop less invasive alternatives to lymph node dissection for prognostic axillary evaluation. The benefit of systematic lymph node dissection for all invasive lesions is now being questioned.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die absoluten Vorteile sind die radiologisch hohe Sicherheit, der Komfort und die Zufriedenheit der Patientin und die vollständige Entfernung der verdächtig-ten Läsion [1][2][3][4][5]8].…”
Section: Zusammenfassung Und Schlussfolgerungunclassified